Functional impact of bilateral vestibular loss and the unexplained complaint of oscillopsia - Geisinger, Dario; Elyoseph, Zohar; Zaltzman, Roy; Mintz, Matti; Gordon, Carlos R. (Frontiers in Neurology, 2024)
Introduction The vestibulo-ocular reflex (VOR) stabilizes vision during head movements. VOR disorders lead to symptoms such as imbalance, dizziness, and oscillopsia. Despite similar VOR dysfunction, patients display diverse complaints. This study analyses saccades, balance, and spatial orientation in chronic peripheral and central VOR disorders, specifically examining the impact of oscillopsia. Methods Participants involved 15 patients with peripheral bilateral vestibular loss (pBVL), 21 patients with clinically and genetically confirmed Machado–Joseph disease (MJD) who also have bilateral vestibular deficit, and 22 healthy controls. All pBVL and MJD participants were tested at least 9 months after the onset of symptoms and underwent a detailed clinical neuro-otological evaluation at the Dizziness and Eye Movements Clinic of the Meir Medical Center. Results Among the 15 patients with pBVL and 21 patients with MJD, only 5 patients with pBVL complained of chronic oscillopsia while none of the patients with MJD reported this complaint. Comparison between groups exhibited significant differences in vestibular, eye movements, balance, and spatial orientation. When comparing oscillopsia with no-oscillopsia subjects, significant differences were found in the dynamic visual acuity test, the saccade latency of eye movements, and the triangle completion test. Discussion Even though there is a significant VOR gain impairment in MJD with some subjects having less VOR gain than pBVL with reported oscillopsia, no individuals with MJD reported experiencing oscillopsia. This study further supports that subjects experiencing oscillopsia present a real impairment to stabilize the image on the retina, whereas those without oscillopsia may utilize saccade strategies to cope with it and may also rely on visual information for spatial orientation. Finding objective differences will help to understand the causes of the oscillopsia experience and develop coping strategies to overcome it.